ANALISIS SPASIAL (TOPOGRAFI) TUBERKULOSIS PARU DI KOTA PARIAMAN, BUKITTINGGI, DAN DUMAI TAHUN 2010-2016 - Arinil Haq; Umar Fahmi Achmadi; Dewi Susanna (Puslitbang Upaya Kesehatan Masyarakat, 2019)
ABSTRACT Tuberculosis (TB) is a disease that has become one of the global concerns. Various factors can increase the incidence of TB and facilitate transmission, one of which is environmental factors. This study aimed to understand the correlation between altitude, population density, and healthy home coverage with the proportion of smear-positive pulmonary TB in Pariaman, Bukittinggi and Dumai in 2010-2016. This study is an ecological study. The data of smear-positive pulmonary TB cases obtained from District Health Office were processed in aggregate at each sub-district in Pariaman, Bukittinggi and Dumai areas. Data were analyzed by correlation test and spatial analysis. The results of this study indicate that there is a strong correlation between altitude with the proportion of smear-positive pulmonary TB in Bukittinggi with direction of the correlation is negative, which mean that the higher the altitude the lower the pulmonary Tb case. It is suggested that area with lower altitude can focus more on promotion and prevention of pulmonary TB through health education or other health promotion measures. Keywords: Spatial analysis, pulmonary TB cases, altitude, population density, healthy home coverage ABSTRAK Tuberkulosis (TB) adalah penyakit yang menjadi salah satu perhatian global. Berbagai faktor dapat meningkatkan kejadian TB dan mempermudah penularan, salah satunya adalah faktor lingkungan. Penelitian ini merupakan studi ekologis yang bertujuan untuk mengetahui korelasi antara ketinggian wilayah, kepadatan penduduk, dan cakupan rumah sehat dengan proporsi TB paru basil tahan asam (BTA) positif di Kota Pariaman, Bukittinggi, dan Dumai tahun 2010-2016. Data dianalisis dengan uji korelasi dan analisis spasial. Hasil penelitian ini menunjukkan bahwa diantara variabel yang diuji, hanya ketinggian wilayah yang berkorelasi kuat dengan proporsi TB paru BTA positif di Kota Bukittinggi. Semakin tinggi wilayah maka semakin rendah kasus TB paru BTA positif di Kota Bukittinggi. Disarankan daerah dengan dataran yang lebih rendah dapat lebih fokus untuk melakukan upaya preventif dan promotif TB paru melalui kegiatan penyuluhan dan upaya promosi kesehatan lainnya. Kata kunci:Analisis spasial, angka kejadian TB paru, ketinggian wilayah, kepadatan penduduk, cakupan rumah sehat